2004
DOI: 10.1095/biolreprod.103.022384
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Estrogenic Effects by Dihydrotestosterone in the Pig Uterus Is Associated with Downregulation of the Estrogen Receptors1

Abstract: Androgens are known to attenuate some effects of estradiol-17beta (E) in the uterus. The objectives of the present experiment were to determine effects of 5alpha-dihydrotestosterone (DHT) on estrogenic actions in the pig uterus and its associations with changes in expression of the estrogen receptor (ER) alpha and ERbeta. Postpubertal gilts (120-130 kg of body weight; n = 16) were ovariectomized, and 3-4 weeks later received once-a-day injections (i.m.) of one of the following treatments during four consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…This study was designed to investigate uterotrophic effects of relaxin when administered beginning either before or after the onset of ERa expression in the neonatal porcine uterus. Recently, evidence was presented for low uterine ERb gene expression in adult porcine uterine tissues detected by quantitative PCR (Cardenas & Pope 2004). Here, immunoblot analysis failed to reveal evidence for ERb expression at the protein level in neonatal uterine tissues.…”
Section: Discussionmentioning
confidence: 79%
“…This study was designed to investigate uterotrophic effects of relaxin when administered beginning either before or after the onset of ERa expression in the neonatal porcine uterus. Recently, evidence was presented for low uterine ERb gene expression in adult porcine uterine tissues detected by quantitative PCR (Cardenas & Pope 2004). Here, immunoblot analysis failed to reveal evidence for ERb expression at the protein level in neonatal uterine tissues.…”
Section: Discussionmentioning
confidence: 79%
“…Reducing AR levels by these various means results in the inhibition of prostate cancer cell growth and PSA expression, while the small interfering RNA knockdown of AR expression also leads to significant apoptotic cell death in androgen-sensitive and AIPC cells (39 -41). Various studies have shown that estrogens have the ability to down-regulate AR expression in different target cells (12,14,42). In particular, studies from our laboratory have shown that MCF-7 breast cancer cells treated with E 2 exhibited significantly lower levels of AR (12).…”
Section: Discussionmentioning
confidence: 88%
“…The ovaries of eight adult Shiba goats (Capra Hircus), (cyclic; n=6 and pregnant; n=2) were excised immediately after euthanasia with an overdose of ketamine during the luteal (Day 10; n=2) and follicular (7,5,3, and 1 day before onset of estrus) phases, and pregnancy (90 and 120 days of gestation). These goats were originated from Animal Resource Science Center, the University of Tokyo (Ibaraki, Japan).…”
Section: Ovaries Sampling Fixation and Slide Preparationmentioning
confidence: 99%
“…Eight-bit images of three random areas of the different ovarian structures were used for semi-quantitative densitometric analysis of immunostaining intensity in the cytoplasm using ImageJ software (National Institutes of Health, available at http://rsb.info.nih.gov/ij/) as previously described [3]. All images were converted to binary (black and white) using the calculated threshold of the currently displayed slice and the integrated intensity was determined using the particle analysis feature of ImageJ.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%